A review of characterisation methods for superabsorbent polymer (SAP) samples to be used in cement-based construction materials: report of the RILEM TC 260-RSC - Schröfl, Christof; Snoeck, Didier; Mechtcherine, Viktor (Materials and structures, 2017)
Superabsorbent polymers (SAPs) have proven to be a very promising admixture which can positively influence various properties of cement-based materials. SAP samples intended for such use should be pre-tested with respect to their absorptivity as well as their kinetics of ab- and desorption prior to implementation in concrete or mortar. This not only reduces workloads in concrete laboratories in pre-testing modified cement-based mixtures but in fact discloses essentials of the eventual performance of the SAP in concrete and other cementitious materials. The review at hand outlines fundamentals of the thermodynamics of polymer chemistry as a basis for the sorptivity tests. The importance of the ionic composition of the test liquids and the interplay among expansive (swelling) and collapse-causing chemical forces in the hydrogel network are highlighted. Methods of free sorptivity testing in adequate saline solutions as well as absorbency determined subject to the application of external forces are summarised. Advantages and drawbacks of these methods are discussed, including a validation of anticipatory evaluations of SAPs’ performance as admixtures in cement-based building materials. Apart from sorptivity pre-tests several methods of instrumental analytics for the chemical characterisation of SAP samples are drawn up, which represent standard approaches of polymer-chemical analytics.